LFA-1 is sufficient in mediating neutrophil emigration in Mac-1-deficient mice. - Lu, H (1997)
To better define the specific function of Mac-1 (CD11b) versus LFA-1 (CD11a) and the other CD11 integrins in vivo, we have disrupted murine CD11b by targeted homologous recombination in embryonic stem cells and generated mice which are homozygous for a mutation in CD11b. A null mutation was confirmed by Southern blotting, RNase protection assay, immunohistochemistry, and flow cytometry. Neutrophils isolated from mice deficient in Mac-1 were defective in adherence to keyhole limpet hemocyanin-coated glass, iC3b-mediated phagocytosis, and homotypic aggregation. When challenged by thioglycollate intraperitoneally, Mac-1-deficient mice had similar levels of neutrophil accumulation in the peritoneal cavity at 1, 2, and 4 h. Treatment with mAb to LFA-1 blocked 78% of neutrophil accumulation in Mac-1-deficient mice and 58% in wild-type mice. Neutrophil emigration into the peritoneal cavity 16 h after the implantation of fibrinogen-coated disks was not reduced in Mac-1-deficient mice whereas neutrophil adhesion to the fibrinogen-coated disks was reduced by > 90%. Neutrophils from Mac-1-deficient mice also showed reduced degranulation. Our results demonstrate that Mac-1 plays a critical role in mediating binding of neutrophils to fibrinogen and neutrophil degranulation, but is not necessary for effective neutrophil emigration, which is more dependent upon LFA-1.